(untitled) (International Journal of Environmental Sciences, 2025)
This study aims to evaluate the effectiveness of the implementation of the Cash for Work Program (PKT) and Business Capital Assistance through Village Funds in encouraging increased employment and business opportunities in Pinrang Regency, South Sulawesi. Although the allocation of Village Funds nationally increased significantly from IDR 20.8 trillion to IDR 72 trillion (2020) and Pinrang Regency received IDR 68.9 billion, regional economic growth actually experienced a downward trend from 8.51% (2012) to only 4.52% (2022). The mismatch between the increase in budget and economic performance shows that the amount of funds does not automatically produce optimal development impacts. Using William N. Dunn’s policy evaluation approach, this study found that the program has provided direct benefits such as temporary job creation and capital support. However, long-term effectiveness has not been achieved due to lack of assistance, coordination constraints, and weak community involvement. The evaluation also revealed that assistance was not adequate (adequacy), not evenly distributed (equity), and not entirely on target (accuracy). Therefore, improvements are recommended in various aspects, including local data-based planning, increasing the capacity of implementers and facilitators, improving the beneficiary verification system, integrating training and business assistance, and developing partnerships and impact-based evaluation systems. This study emphasizes the importance of participatory governance and strengthening village institutional capacity to realize sustainable economic development, and provides theoretical contributions through the integration of Dunn’s evaluation approach in the context of village-based policies.